The College of Aeronautics whirling arm initial development tests - Kumar, P. E. (College of Aeronautics, 1967)
The old Whirling Arm o-r the National Physical Laboratory has been re-erected at the College to provide a facility for the study of ground effect on wings, and other craft operating near the ground. The model is mounted on struts, which differ considerably from those used by N.P.L., and moves over an adjustable floor in a specially constructed Channel. This note covers the initial tests conducted on the arm towards making it a fully operational facility. It-is concluded that a full yaw-meter survey is necessary to define the air-flow existing in the channel, during operation of the arm, and that the instrumentation being used needs to be further developed.